Eating occasion situational factors and sugar-sweetened beverage consumption in young adults - McNaughton, Sarah A. (Int J Behav Nutr Phys Act, 2020)
BACKGROUND: Young adulthood represents an influential transitional period marked by poor dietary habits and excess weight gain. Sugar-sweetened beverages (SSB) are a major source of excess caloric intake among young adults, yet little is known about the correlates of SSB consumption. This study examines the individual and situational correlates of SSB consumption, using real-time assessment of Australian young adults’ eating occasions. METHODS: Dietary, sociodemographic and health behaviour data were collected during the Measuring EAting in Everyday Life (MEALS) study (n = 675 adults, 18–30 y). Participants reported all foods and beverages consumed over 3–4 non-consecutive days using a real-time Smartphone food diary application (“FoodNow”). For every eating occasion, food and beverage intake was recorded along with situational characteristics (eating location, purchase location, presence of others and activities while eating). A beverage occasion was defined as any eating occasion where a beverage was consumed and a SSB occasion was defined as any eating occasion where a SSB was consumed. Multilevel logistic regression was used to examine individual and situational characteristics with SSB intake at beverage occasions (i.e. factors associated with choosing a SSB over other non-alcoholic beverages) and to examine factors associated with consuming a SSB at any occasion where food and/or beverages were consumed. RESULTS: Thirty-five percent of participants consumed SSBs during the recording period (n = 237). Of the 2185 beverage eating occasions reported by SSB consumers, 481 (20%) contained a SSB. SSB were rarely consumed on their own (i.e. other foods were present). Having a lower than tertiary education (odds ratio [95% confidence interval]: 1.53 [1.16, 2.01]; p < 0.01); eating in a café/restaurant, compared to at home (3.02 [1.58, 5.78]; p < 0.001), and purchasing beverages from a convenience outlet, compared to a supermarket/grocery store (4.58 [2.85, 7.38]; p < 0.001) were associated with SSB intake at beverage eating occasions. Similar associations were also found when all food and/or beverage eating occasions were examined. CONCLUSION: In this study, SSB were often consumed with other foods and intake was associated with individual and situational factors. Further studies are needed to confirm these findings and explore how SSB are consumed in relation to their accompanying foods.